Why aren't more veterinary practices owned or led by women? - Treanor, Lorna (BMJ Publishing Group, 2016)
The increasing proportion of women among the body of UK veterinary surgeons practicing clinical medicine has been consistently highlighted in RCVS surveys (RCVS 2006, 2010, 2014a). Despite women outnumbering men in clinical practice (57% v 43%) in 2014 (RCVS, 2014a) they do not own veterinary practices or hold practice partnerships or leadership positions in proportions that may be expected, even when adjusting for age and experience (RCVS, 2014b).